The shadow in the balance sheet: The spectre of Enron and how accountants use the past as a psychological defence against the future - Cooper, David; James, Kim; Kwiatkowski, Richard; Taffler, Richard J. (Cranfield University, 2004)
Accounting frameworks play a crucial role in enabling us to make sense of business. These frameworks provide a common language for individuals, organizations and broader economic groupings to understand and make decisions about the commercial realm in which they operate. From a psychodynamic perspective, the language of accounting also plays an important role. On the one hand it offers a way to tame the uncertainty and unknowability of the future by representing it in the same comforting terms as it does the past, thus reducing anxiety. Accounting provides a ‘shorthand’, which achieves a balance between positive and negative, debit and credit, asset and liability. On the other hand, accounting can also provide an arena in which fantasies about the future can be staged. However, the use of accounting language is problematic, particularly when it comes to dealing with the future. First, accounting frameworks are inherently backward looking and second, the reassuring sense of clarity and predictability they give are bought at the price of unrealistic simplification. The shadow is never far away and is a constant source of surprises in the unfolding future of a business. Rationalizing and sanitizing the shadow through accounting language may alleviate anxiety but fails to provide an escape from its effects, and echoes from the shadow side of business are capable of shaking the world in the form of accounting scandals. Governments and businesses have reacted to scandals such as Enron and Worldcom by tightening legislation and refining accounting standards but little, if anything, has been done to bring us any closer to confronting the shadow of business where these scandals have their ro
Keywords: Shadow; Accounting; Intangibles; Systems Psychodynamics; Defence Mechanism